Mortality rate of people exposed to Mustard Gas during Iran-Iraq war in Sardasht, Iran: a 32 years retrospective cohort study - Mohammad Hasan Rabiee; Mostafa Ghanei; Hossein Amini; Aliasghar Akhlaghi (BMC, 2022)
Abstract Background Mustard gas (MG) is one of the most widely used chemical weapons in the past century. However, little information exists concerning long-term mortality from MG exposure. In this study, we investigated mortality rate among civilian people exposed to MG during Iran-Iraq war in Sardasht in Iran after 32 years.  Methods In this retrospective cohort study, data of people exposed to MG in Sardasht in 1987 were extracted from the Veterans and Martyr Affair Foundation of Iran up to March 20, 2019. Mortality rate, cumulative mortality and standardized mortality ratio with 95% confidence interval were calculated to explain mortality in the cohort, and then compared with general Iranian population. Cox regression analysis was used to indicate factor affecting the risk of death in the cohort.  Results Out of 1,203 exposed people at the beginning of the period, 148 people died by the end of the study, with an average age of 66.42 at the time of death. Total person-years of the people up to end of the study were 38,198.63 and mortality rate was equal to 387 per 100,000 persons-years. Total number of observed deaths was less than expected death and the all-cause standardized mortality ratio (SMR) was determined as 0.680 (95% CI: 0.574 - 0.798). Cause-specific SMR showed that observed death due to respiratory diseases was higher than expected (SMR: 1.75) (95% CI: 1.145 - 2.569). The results of univariate and multivariate cox regression analysis showed that increasing age and having severe late complications in lung were associated with increased risk of death among people in the cohort. Conclusion In general, this result indicated that acute exposure to MG, even without wearing protective clothing and masks, could not increase all-cause mortality after 32 years if accompanied by special and ongoing care for those exposed.